Golgi defect as a major contributor to lysosomal dysfunction - Akaaboune, Sarah R.; Wang, Yanzhuang (Frontiers in Cell and Developmental Biology, 2024)
The Golgi apparatus plays a crucial role in lysosome biogenesis and the delivery of lysosomal enzymes, essential for maintaining cellular homeostasis and ensuring cell survival. Deficiencies in Golgi structure and function can profoundly impact lysosomal homeostasis, leading to various lysosomal storage diseases and neurodegenerative disorders. In this review, we highlight the role of the Golgi Reassembly Stacking Proteins (GRASPs) in the formation and function of the Golgi apparatus, emphasizing the current understanding of the association between the Golgi apparatus, lysosomes, and lysosomal storage diseases. Additionally, we discuss how Golgi dysfunction leads to the secretion of lysosomal enzymes.This review aims to serve as a concise resource, offering insights into Golgi structure, function, diseaserelated defects, and their consequential effects on lysosomal biogenesis and function. By highlighting Golgi defects as an underappreciated contributor to lysosomal dysfunction across various diseases, we aim to enhance comprehension of these intricate cellular processes.